Nucleolar and spindle associated protein 1 enhances chemoresistance through DNA damage repair pathway in chronic lymphocytic leukemia by binding with RAD51 - Yang Han (Nature Publishing Group, 2021)
Abstract Nucleolar and spindle-associated protein 1 (NUSAP1) is an essential regulator of mitotic progression, spindle assembly, and chromosome attachment. Although NUSAP1 acts as an oncogene involved in the progression of several cancers, the exact role of chronic lymphocytic leukemia (CLL) remains elusive. Herein, we first discovered obvious overexpression of NUSAP1 in CLL associated with poor prognosis. Next, the NUSAP1 level was modulated by transfecting CLL cells with lentivirus. Silencing NUSAP1 inhibited the cell proliferation, promoted cell apoptosis and G0/G1 phase arrest. Mechanistically, high expression of NUSAP1 strengthened DNA damage repairing with RAD51 engagement. Our results also indicated that NUSAP1 knockdown suppressed the growth CLL cells in vivo. We further confirmed that NUSAP1 reduction enhanced the sensitivity of CLL cells to fludarabine or ibrutinib. Overall, our research investigates the mechanism by which NUSAP1 enhances chemoresistance via DNA damage repair (DDR) signaling by stabilizing RAD51 in CLL cells. Hence, NUSAP1 may be expected to be a perspective target for the treatment of CLL with chemotherapy resistance.